(untitled) (American Journal of Interdisciplinary Research and Innovation, 2022)
Language capability stands for a learner’s competence to use a language spontaneously and subconsciously in different situations. Skill on spoken English is extensively significant for any type of communication and correspondence. The need of spoken English is indefinable in the fields of refined education process both at home and abroad, better career opening, smart business, global communication, information and technology and better survival. It’s a deliberate process to steep capableness of English language into learners since their pre-primary tutoring to undergraduate echelon. It’s apparent in the course and syllabus of Intermediate stratum in Bangladesh that the sole emphasis has been put only on reading and writing whilst listening and speaking proficiency are remaining dark, whereas speaking skill is indispensible for transnational communication, advanced study at home and abroad, professional and business purpose, operating information and communication technology, pursuing better career etc. In this regard, lack of provocation to learn and exercise, unconstructive tutoring outfit, testing strategy excepting spoken predicated outgrowths along with marks distribution and paucity of experienced instructors in English and so on are the crucial deficits behind this problem. It’s a study targeting at assessing the spoken capability of the 12 class pupils in Rangpur Division of Bangladesh. This qualitative inquest work took place in the month of April 2022 and June 2022. The 100 informants were selected right away. Out of 100 interviewees, 50 were from urban and 50 were from rural intermediate standing institutions of 8 Districts in Rangpur Division of Bangladesh. A Spoken Test on free speech for the pupils was carried out by the author. Their speaking perfection was tested through content analysis to evoke data. The result focused that the replier made desultory errors in great number on fluency, vocabulary, information, sequence of tenses, sub-verb agreement, applicability and treatment of words, use of preposition, intonation and pronunciation. As per data compilation, it was noticed that deficits made in the process were almost on part of the rural participants. In addition, phobia in speaking English and irrelevancy were two peculiar limitations among the pupils hailing from rural background institutions.